1998
DOI: 10.1002/(sici)1096-9896(199808)185:4<427::aid-path127>3.0.co;2-7
|View full text |Cite
|
Sign up to set email alerts
|

Immunocytochemical detection of isolated epithelial cells in bone marrow: non-specific staining and contribution by plasma cells directly reactive to alkaline phosphatase

Abstract: Detection of isolated tumour cells (TCs) in bone marrow (BM) from epithelial cancer patients by immunocytochemical (ICC) analysis seems to predict future relapse, but the reported percentages of positive BMs among patients with localized cancer show large variations and the number of detected TCs is low. This emphasizes the importance of thoroughly testing the methods in use. This study was performed to clarify to what extent positive staining of haematopoietic cells (HCs) interferes with the ICC detection of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
82
0
2

Year Published

1998
1998
2006
2006

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 132 publications
(86 citation statements)
references
References 30 publications
(52 reference statements)
2
82
0
2
Order By: Relevance
“…MMG is a protein associated with most breast cancers, and RT-PCR determination of MMG expression in BM has been found to be specific and sensitive. 24 Its expression may inversely correlate with tumor burden and prognosis. 30 We elected to study BM rather than peripheral blood cells for several reasons: firstly, bone and BM are usual sites of metastasis by breast cancer; secondly, most studies to date have focused on BM micrometastases, and have found a correlation among presence of tumor cells and survival; [15][16][17][18] thirdly, guidelines for analysis and evaluation of isolated tumor cells in the BM have been issued by a scientific society (ISHAGE, now ISCT); 31 and finally, BM samples were already available because of chimerism analysis, without the need to perform fastidious ad hoc sampling.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…MMG is a protein associated with most breast cancers, and RT-PCR determination of MMG expression in BM has been found to be specific and sensitive. 24 Its expression may inversely correlate with tumor burden and prognosis. 30 We elected to study BM rather than peripheral blood cells for several reasons: firstly, bone and BM are usual sites of metastasis by breast cancer; secondly, most studies to date have focused on BM micrometastases, and have found a correlation among presence of tumor cells and survival; [15][16][17][18] thirdly, guidelines for analysis and evaluation of isolated tumor cells in the BM have been issued by a scientific society (ISHAGE, now ISCT); 31 and finally, BM samples were already available because of chimerism analysis, without the need to perform fastidious ad hoc sampling.…”
Section: Discussionmentioning
confidence: 99%
“…23 Immunocytochemistry is relatively easy to apply, not requiring sophisticated devices, and standardization criteria have been reported. 24 We have recently found that a nested RT-PCR assay for the expression of maspin and mammaglobin (MMG) genes is a sensitive and specific assay for detection of breast cancer cells in the BM. 25 In comparison with immunocytochemical assay, RT-PCR has the advantage of being operator-independent, and allows a permanent record of the results.…”
Section: Introductionmentioning
confidence: 99%
“…Also the different immunocytochemical procedures used in the various studies might be a source of bias. Different patterns of specificity and sensitivity among the various MoAbs used are known to influence the tumour-cell detection (Borgen et al, 1998;Page et al, 1999). Due to these problems, also in gastric cancer there was a wide range of positivity (from 25% to 53%).…”
Section: Cytokeratin-positive Cells In Bone Marrow Of Gastric Cancer mentioning
confidence: 99%
“…The magnitude of 10 6 mononuclear cells has been shown to provide a higher probability of detecting even one or two positive cells (Borgen et al, 1998;Funke and Schraut, 1998). Another aspect that might be a source of pitfalls is that during the cytospin procedure there is a loss of mononuclear cells and the number of cells rescued on the slides is lower than that counted in the suspension before starting the procedure.…”
Section: Ck-ck+mentioning
confidence: 99%
See 1 more Smart Citation